A Mini Review on the Electrical Components for Energy Consumption - Ibrahim, Nur Aifiah Binti (Darul Yasin Al Sys, 2025)
Energy can either be stabilised or not by introducing the new portable device for cloud computing using Android in applicable software. Software engineers are researching the most ideal type of telecommunication device and energy mass production in supporting communities' daily activities. At first, raw information is then, edited and coded for external use in data analyses. Chances of getting it done are first, to measure the risks and problems in addressing the gap of using the current and latest technology during the era. Judging by the vehicle and traffic system, safety first so as, other factors of management in terms of radio transmission and signals to the bumpy cars from behind. The car parts are continuously manufactured as the metallic and synthetic fibers are traded and shipped from a foreign country ended up in the stores as the momentum in demand and supply slows down for turnover in resource allocation. Therefore, sustainability for the growth of the company must ensure uniqueness and continuous customer satisfaction in making it the best treatment option for them without repurposing their needs and recommendations for business development.